Optimizing nitrogen scheduling, plant geometry, and biofertilizer inoculation for enhanced productivity and soil health of pearl millet (Pennisetum glaucum L.) - BHAVANA .; BALJINDER SINGH; KANIK KUMAR BANSAL; DINESH KUMAR (Research on Crops, 2026)
Pearl millet is a major cereal crop of the semi-arid regions; however, its productivity is constrained by low nitrogen-use efficiency, suboptimal plant geometry, and poor soil fertility. Therefore, optimising nitrogen scheduling, plant geometry, and biofertilizer inoculation is essential to enhance productivity, nutrient uptake, soil health, and profitability under semi-arid conditions. An experiment was conducted during the kharif seasons of 2023 and 2024 at Rohtak, Haryana, India, to evaluate the effect of nitrogen scheduling, plant geometry, and microbial inoculation on yield, nutrient uptake, soil health, and economics of pearl millet. The experiment was laid out in factorial randomized block design with three replications comprising three nitrogen scheduling treatments, two plant geometries, and three microbial inoculation treatments. Results revealed that application of nitrogen in three splits significantly improved grain yield, grain nitrogen uptake, protein content, and post-harvest soil available nitrogen compared to a single basal application. Wider spacing of 60 × 15 cm recorded higher grain yield and net returns over closer spacing. Combined inoculation with Azospirillum + phosphate-solubilising bacteria + arbuscular mycorrhiza significantly enhanced microbial biomass carbon, nutrient uptake, and grain quality. The integrated treatment also produced the highest economic returns with a benefit:cost ratio.